Kolangitis Akut Sebagai Kegawatdaruratan Hepatobilier: Pendekatan Diagnosis Berdasarkan Tokyo Guidelines 2018 dan Tata Laksana Awal di Instalasi Gawat Darurat pada Pasien Dewasa - Isnaeni Robiah Aldawiyah; Nugroho Budi Santoso; Rika Bur (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Acute cholangitis is a hepatobiliary emergency caused by bacterial infection of the biliary tract secondary to biliary obstruction. Delayed diagnosis and treatment may lead to sepsis, multiple organ dysfunction, and death. This literature review aims to summarize the anatomy and physiology of the biliary system, pathophysiology, risk factors, clinical manifestations, diagnosis, severity assessment, and emergency management of acute cholangitis in adults based on the Tokyo Guidelines 2018 (TG18). The review was conducted through the analysis of scientific articles, international clinical guidelines, and relevant medical textbooks. According to TG18, diagnosis is established using three categories: systemic inflammation, cholestasis, and imaging findings, while severity is classified into Grade I, II, or III to guide treatment decisions. Initial management includes hemodynamic stabilization, fluid resuscitation, blood culture collection followed by early empirical broad-spectrum antibiotics, appropriate laboratory and imaging evaluation, and timely biliary drainage, preferably by Endoscopic Retrograde Cholangiopancreatography (ERCP). Early diagnosis, accurate severity assessment, effective infection control, and prompt relief of biliary obstruction are essential to improving clinical outcomes. Consistent implementation of TG18 supports systematic emergency management and reduces complications and mortality in adult patients with acute cholangitis.